Rapid assessment of avoidable blindness in a district in central India: the survey findings - Dhawan, Bodhraj; Dhawan, Vaishali B.; Shukla, Ajay Kumar (International Journal Of Community Medicine And Public Health, 2020)
Background: Rapid assessment of avoidable blindness gives an estimate of burden of blindness and causes thereof. Aim of the study was to estimate prevalence of blindness and trends and outcome of cataract surgery in rural India using cluster sample survey. Methods: 30 clusters of 100 people aged above 50 years were selected by stratified cluster sampling. Participants were evaluated for history, vision and dilated fundus examination as per pre designed proforma. Results: Of the 3000 people listed severe visual impairment (visual acuity <3/60) was noted in 134 (4.5%) individuals (361 (6.02%) eyes). Blindness was noted in 107 (3.5%) individuals (483 (8.05%) eyes). Cataract was the most common cause of visual impairement in 18.57% eyes. Pseudophakia was present in 551 (9.2%) eyes and 179 (3.0%) eyes had aphakia. Grade III and Grade IV PCO was noted in 52 (9.4%) and 14 (2.5%) eyes respectively. Conclusions: Untreated cataract continues to be the leading cause of avoidable blindness. Startegies are required to manage blindness following cataract while we plan to combat cataract related blindness.